Feasibility and safety of transradial coronary interventions using a 6.5‐F sheathless guiding catheter in patients with small radial arteries. Issue 1 (30th March 2015) - Cheaito, Radi; Benamer, Hakim; Hovasse, Thomas; Tritar, Amine; Hage, Fouad; Garot, Philippe; Lefèvre, Thierry; Unterseeh, Thierry; Chevalier, Bernard; Morice, Marie‐Claude; Louvard, Yves
<x xml:space="preserve">Abstract</x> Objectives This study investigated the feasibility and the safety of using a 6.5‐French sheathless guide catheter in patients with small radial arteries. Background The small size of radial arteries is a limitation of transradial coronary intervention. A new sheathless guiding catheter with a diameter almost 2‐Fr smaller than conventional sheaths and a full‐length hydrophilic coating has been introduced. Methods A total of 148 patients from three French hospitals were consecutively enrolled from March 2009 to February 2012. They underwent transradial approach (TRA) for percutaneous coronary interventions (PCI) using the 6.5‐F ASAHI sheathless Eaucath guiding catheter system. Results Among the 148 patients enrolled, 95 were females (64%), and 183 lesions were treated. Procedural success rate was 100%. Thirteen patients (9%) underwent same‐procedure multivessel interventions for the right and left coronary artery. Among the group of 46 patients undergoing bifurcation PCI, 35 (76%) bifurcated lesions were treated with a kissing balloon technique, one patient had a saphenous vein bypass graft lesion requiring filter wire placement prior to intervention, nine (6.1%) patients required rotational atherectomy, thrombus‐aspiration catheters were used in 19 (12.8%) patients, fractional flow reserve (FFR)‐guided PCI in 10 (6.7%) patients, alcohol septal ablation in three (2%) patients. Ten (6.7%) cases of chronic total occlusion were successfully treated in nine (6.1%) patients using the hydrophilic catheter. No radial artery site complications was noted. Conclusion The use of sheathless guiding catheters is a safe, effective method for PCI via TRA in small radial arteries without catheter‐related complications. © 2015 Wiley Periodicals, Inc.